(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Diabetes mellitus is a metabolic disorder affecting many organs of the body with severs complication if untreated. In India, diabetes is leading major disorder mainly affecting in the urban areas due to change of life style, lack of attention towards exercise and hectic schedule. There is huge availability of allopathic medicines for better treatment but have side effects also. Indian traditional herbs are also used from ancient times for different treatment. Herbal formulations for diabetes are the proven and effective medicines in India and variety of medicinal plant are used to treat complications of diabetes. These Ayurvedic plants and parts of plants have different chemical constituents and can be used as a medicine. These contents also have a rich sources of antioxidant property that used to control the free radical formation. In this research review, our aim is to cover traditional herb and plants from India having anti-diabetes activity, its chemical constitution and active ingredients used for treatment. These plants if we start to used with or without allopathic drug treatment on daily basis can make big differences for control and management of diabetes.